1985
DOI: 10.1111/j.1651-2227.1985.tb10951.x
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment of Some Microflora Associated Biochemical Characteristics in Feces from Children during the First Years of Life

Abstract: This report presents a new approach to the study of the colonization of the digestive tract after birth. We have examined the development of four microflora associated characteristics, MACs, defined as the recording of any anatomical structure, biochemical or physiological function in the macroorganism, which has been influenced by the microflora. These MACs may create a basis for later investigations into the impact of diarrheal diseases and antibiotic therapy. The following biochemical characteristics were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 12 publications
2
35
0
1
Order By: Relevance
“…The establishment of a mucindegrading flora in the human colon is a gradual process that begins in some infants as early as 3 mo of age (17,18). In the study of structures as complex as mucins, it may be difficult to determine whether changes in composition are the result of differences in their synthesis or bacterial degradation or of the analytical techniques used.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a mucindegrading flora in the human colon is a gradual process that begins in some infants as early as 3 mo of age (17,18). In the study of structures as complex as mucins, it may be difficult to determine whether changes in composition are the result of differences in their synthesis or bacterial degradation or of the analytical techniques used.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal development of the GIT bacterial assemblages is complex [32,33] , involves changes in the absolute and relative abundances of species [34][35][36][37] and metabolic processes [38] . Notable are the changes in the abundances of naturally occurring species of lactobacilli in the intestines of pigs [39] and human infants [34] , and for probiotic bacteria introduced into the neonatal GIT [37 , present study].…”
Section: Discussionmentioning
confidence: 99%
“…Mucin degradation has been recognized as a normal process of mucus turn-over in the GI tract, starting a few months after birth. 78 Midtvedt et al studied the establishment of the mucin-degrading microbiota from 30 Swedish children from birth to the age of two years old, by analyzing their fecal samples. They found that the establishment of mucin-degrading bacteria starts during the first months of life, and is completed when the children are around two years old.…”
Section: Mucin Binding By Bacteriamentioning
confidence: 99%